Optimizing the Role of Bhabinkamtibmas Through Guidance and Counseling Activities to Reduce Fraud in the Kediri City Police - Rendhi Alannugraha Sugiarto; Fauzan, Muhammad Shidqy; Iqbal, Mohammad (Tanggon Kosala, 2025)
This research is motivated by the high incidence of fraud in the jurisdiction of the Kediri Kota Police Resort, which requires preventive efforts to anticipate the issue. The study aims to analyze the implementation of guidance and counseling activities of Bhabinkamtibmas to prevent fraud, as well as the competence and communication of Bhabinkamtibmas in preventing fraud in the area. The theories and concepts used include management, competence, social communication, optimization, role, and the Bhabinkamtibmas concept, with a qualitative method. The results show that although the guidance and counseling activities of Bhabinkamtibmas have been implemented with good operational performance management, there are still limitations in community involvement, lack of impact of the activities, and issues in information dissemination. The competence of Bhabinkamtibmas appears to be good in terms of knowledge, skills, and attitude, but is hindered by heavy workload. Communication by Bhabinkamtibmas in guidance and counseling activities is well-implemented. However, fluctuations in the number of uncovered fraud cases are still found, indicating challenges that must be addressed in fraud prevention efforts.